CircUBXN7 promotes macrophage infiltration and renal fibrosis associated with the IGF2BP2-dependent SP1 mRNA stability in diabetic kidney disease - Lin, Ziyue; Lv, Dan; Liao, Xiaohui; Peng, Rui; Liu, Handeng; Wu, Tianhui; Wu, Keqian; Sun, Yan; Zhang, Zheng (Frontiers in Immunology, 2023)
Inflammatory cell infiltration is a novel hallmark of diabetic kidney disease (DKD), in part, by activated macrophages. Macrophage-to-tubular epithelial cell communication may play an important role in renal fibrosis. Circular RNAs (circRNAs) have been reported in the pathogenesis of various human diseases involving macrophages activation, including DKD. However, the exact mechanism of circRNAs in macrophage infiltration and renal fibrosis of DKD remains obscure. In our study, a novel circRNA circUBXN7 was identified in DKD patients using microarray. The function of circUBXN7 in vitro and in vivo was investigated by qRT-PCR, western blot, and immunofluorescence. Finally, a dual-luciferase reporter assay, ChIP, RNA pull-down, RNA immunoprecipitation and rescue experiments were performed to investigate the mechanism of circUBXN7. We demonstrated that the expression of circUBXN7 was significantly upregulated in the plasma of DKD patients and correlated with renal function, which might serve as an independent biomarker for DKD patients. According to investigations, ectopic expression of circUBXN7 promoted macrophage activation, EMT and fibrosis in vitro, and increased macrophage infiltration, EMT, fibrosis and proteinuria in vivo. Mechanistically, circUBXN7 was transcriptionally upregulated by transcription factor SP1 and could reciprocally promote SP1 mRNA stability and activation via directly binding to the m6A-reader IGF2BP2 in DKD. These results reveal that circUBXN7 may provide the potential biomarker and therapeutic target for DKD.